2008
DOI: 10.1073/pnas.0711496105
|View full text |Cite
|
Sign up to set email alerts
|

Role of GSK3β in behavioral abnormalities induced by serotonin deficiency

Abstract: Dysregulation of brain serotonin (5-HT) neurotransmission is thought to underlie mental conditions as diverse as depression, anxiety disorders, bipolar disorder, autism, and schizophrenia. Despite treatment of these conditions with serotonergic drugs, the molecular mechanisms by which 5-HT is involved in the regulation of aberrant emotional behaviors are poorly understood. Here, we generated knockin mice expressing a mutant form of the brain 5-HT synthesis enzyme, tryptophan hydroxylase 2 (Tph2). This mutant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
321
4
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(359 citation statements)
references
References 54 publications
(92 reference statements)
28
321
4
6
Order By: Relevance
“…Most relevant to our study are results from their heterozygous 1449A mice, in which 5-HT synthesis was only reduced by 40% (Beaulieu et al, 2008). This decrease is comparable to the reduction of 5-HT synthesis detected in our 1473G/G mice.…”
Section: Mouse Tph2 Polymorphisms In Defined Genetic Backgroundssupporting
confidence: 68%
See 3 more Smart Citations
“…Most relevant to our study are results from their heterozygous 1449A mice, in which 5-HT synthesis was only reduced by 40% (Beaulieu et al, 2008). This decrease is comparable to the reduction of 5-HT synthesis detected in our 1473G/G mice.…”
Section: Mouse Tph2 Polymorphisms In Defined Genetic Backgroundssupporting
confidence: 68%
“…We demonstrate that 1473G/G mice show a distinct anxiety phenotype, which could be observed in four different anxiety tests. A rare human G1463A TPH2 SNP was analyzed via a knock-in approach in transgenic mice (Beaulieu et al, 2008;Jacobsen et al, 2011). Mice homozygous for the corresponding mouse Tph2 allele 1449A showed an 80% reduction of 5-HT synthesis and a strong decrease in total and extracellular 5-HT concentrations.…”
Section: Mouse Tph2 Polymorphisms In Defined Genetic Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic unpredictable stress further aggravates these traits. The impulsive and hyperaggressive behaviour of Tph2 2/2 mice resembles the increased defensiveness reported for Pet1 KO [17] and Tph2 R439H mutants [19]. Acute treatment with 5-HT 1A and 5-HT 1B receptor agonists (or 5-HT 2A/2C antagonists) via their inhibitory action on neurotransmission (pre-synaptically or post-synaptically) was reported to reduce aggressive behaviour, and it was suggested that low 5-HT levels in the brain are associated with maladaptive forms of excessive violence rather than with natural defensiveness [3].…”
Section: Tph2 In Personality Traits Of Negative Emotionality and In Dmentioning
confidence: 99%